Research Resource: Global Identification of Estrogen Receptor β Target Genes in Triple Negative Breast Cancer Cells - Shanle, Erin K. (Endocrine Society, 2013)
Breast cancers that are negative for estrogen receptor α (ERα), progesterone receptor, and human epidermal growth factor receptor 2 are known as triple-negative breast cancers (TNBC). TNBCs are associated with an overall poor prognosis because they lack expression of therapeutic targets like ERα and are biologically more aggressive. A second estrogen receptor, ERβ, has been found to be expressed in 50% to 90% of ERα-negative breast cancers, and ERβ expression in TNBCs has been shown to correlate with improved disease-free survival and good prognosis. To elucidate the role of ERβ in regulating gene expression and cell proliferation in TNBC cells, the TNBC cell line MDA-MB-468 was engineered with inducible expression of full-length ERβ. In culture, ERβ expression inhibited cell growth by inducing a G1 cell cycle arrest, which was further enhanced by 17β-estradiol treatment. In xenografts, ERβ expression also inhibited tumor formation and growth, and 17β-estradiol treatment resulted in rapid tumor regression. Furthermore, genomic RNA sequencing identified both ligand-dependent and -independent ERβ target genes, some of which were also regulated by ERβ in other TNBC cell lines and correlated with ERβ expression in a cohort of TNBCs from the Cancer Genome Atlas Network. ERβ target genes were enriched in genes that regulate cell death and survival, cell movement, cell development, and growth and proliferation, as well as genes involved in the Wnt/β-catenin and the G1/S cell cycle phase checkpoint pathways. In addition to confirming the anti-proliferative effects of ERβ in TNBC cells, these data provide a comprehensive resource of ERβ target genes and suggest that ERβ may be targeted with ligands that can stimulate its growth inhibitory effects.